Personal distress and empathic concern in methadone-maintained patients. (2nd January 2017) - Tomei, Alexander; Besson, Jacques; Reber, Nadia; Rougemont-Bücking, Ansgar; Grivel, Jeremy
Abstract: The purpose of the present study is to contribute to the understanding of empathy in people with addictive disorders. Previous studies have shown decreased empathy in people suffering from addiction to alcohol, cocaine, and methamphetamine and in people consuming combinations of addictive substances. Here, we compare empathy in a sample of methadone-maintained patients (MMPs) to a group of healthy controls by using the Interpersonal Reactivity Index (IRI). The analyses showed that MMPs had lower empathic concern and higher personal distress compared to healthy controls. Our findings expand on previous evidence of opiate addiction corresponding to high personal distress and low empathic concern for this psychiatric condition. They also underline the relevance of measuring personal distress when assessing empathy in populations suffering from similar disorders.